Hypomagnesemia in short bowel syndrome patients - Miranda, Simone Chaves; Ribeiro, Michelle Lizzy Bandeira; Ferriolli, Eduardo; Marchini, Júlio Sérgio (São Paulo Medical Journal, 2000)
CONTEXT: Magnesium support to small bowel resection patients. OBJECTIVE: Incidence and treatment of hypomagnesemia in patients with extensive small bowel resection. DESIGN: Retrospective study. SETTING: Metabolic Unit of the University Hospital Medical School of Ribeirão Preto, University of São Paulo, Brazil. PATIENTS: Fifteen patients with extensive small bowel resection who developed short bowel syndrome. MAIN MEASUREMENTS: Serum magnesium control of patients with bowel resection. Replacement of magnesium when low values were found. RESULTS: Initial serum magnesium values were obtained 21 to 180 days after surgery. Hypomagnesemia [serum magnesium below 1.5 mEq/l (SD 0.43)] was detected in 40% of the patients [1,19 mEq/l (SD 0.22)]. During the follow-up period, 66% of the patients presented at least two values below reference (1.50 mEq/l). 40% increased their serum values after magnesium therapy. CONCLUSION: Metabolic control of serum magnesium should be followed up after extensive small bowel resection. Hypomagnesemia may be found and should be controlled.